Beta‐blocker use and fall risk in older individuals: Original results from two studies with meta‐analysis. (4th July 2017) - Ham, Annelies C.; van Dijk, Suzanne C.; Swart, Karin M. A.; Enneman, Anke W.; van der Zwaluw, Nikita L.; Brouwer‐Brolsma, Elske M.; van Schoor, Natasja M.; Zillikens, M. Carola; Lips, Paul; de Groot, Lisette C. P. G. M.; Hofman, Albert; Witkamp, Renger F.; et al.
Abstract : Aims: To investigate the association between use of β‐blockers and β‐blocker characteristics – selectivity, lipid solubility, intrinsic sympathetic activity (ISA) and CYP2D6 enzyme metabolism – and fall risk. Methods: Data from two prospective studies were used, including community‐dwelling individuals, n  = 7662 (the Rotterdam Study) and 2407 (B‐PROOF), all aged ≥55 years. Fall incidents were recorded prospectively. Time‐varying β‐blocker use was determined using pharmacy dispensing records. Cox proportional hazard models adjusted for age and sex were applied to determine the association between β‐blocker use, their characteristics – selectivity, lipid solubility, ISA and CYP2D6 enzyme metabolism – and fall risk. The results of the studies were combined using meta‐analyses. Results: In total 2917 participants encountered a fall during a total follow‐up time of 89 529 years. Meta‐analysis indicated no association between use of any β‐blocker, compared to nonuse, and fall risk, hazard ratio (HR) = 0.97 [95% confidence interval (CI) 0.88–1.06]. Use of a selective β‐blocker was also not associated with fall risk, HR = 0.92 (95%CI 0.83–1.01). Use of a nonselective β‐blocker was associated with an increased fall risk, HR = 1.22 (95%CI 1.01–1.48). Other β‐blocker characteristics including lipid solubility and CYP2D6 enzyme metabolism were not associated with fall risk. Conclusion: Our study suggests that use of a nonselective β‐blocker, contrary to selective β‐blockers, is associated with an increased fall risk in an older population. In clinical practice, β‐blockers have been shown effective for a variety of cardiovascular indications. However, fall risk should be considered when prescribing a β‐blocker in this age group, and the pros and cons for β‐blocker classes should be taken into consideration.